Editorial (2018)
In this issue of Revista Activos (Activos Journal), the Valuation of companies and business management has been defined as a central theme. It is well known that, in recent years, the growing dynamics of mergers and acquisitions have made it imperative to find fair values for companies. Under this scenario it is highlighted that the monetary representation of a company is not specifically reflected solely by its equity composition, but depends on other variables such as its trajectory, the levels of risk it manages, its short and long-term economic and financial capacity, the socio-economic environment in which it operates and other intangible characteristics that express its true value.